ChemInform Abstract: Pontemazines A and B, Phenazine Derivatives Containing a Methylamine Linkage from Streptomyces sp. UT1123 and Their Protective Effect to HT‐22 Neuronal Cells. Issue 10 (February 2016) - Cha, Jin Wook; Lee, Seung Il; Kim, Min Cheol; Thida, Mya; Lee, Jae Wook; Park, Jin‐Soo; Kwon, Hak Cheol
Abstract: Pontemazines A (Ia) and B (Ib) possess a neuronal cell protective effect on glutamate‐induced mouse hippocampal HT‐22 cell damage.